Languages and compilers for parallel computing : 30th International Workshop, LCPC 2017, College Station, TX, USA, October 11-13, 2017 : revised selected papers /: 30th International Workshop, LCPC 2017, College Station, TX, USA, October 11-13, 2017 : revised selected papers. ([2019]) - Unknown
No abstract available